2018
DOI: 10.1002/jcp.27092
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cellular and humoral immune responses to alkaline phosphatase from fertile hydatid cysts in the human peripheral blood

Abstract: Hydatid cyst, the larval stage of the tapeworm Echinococcus granulosus and a causative agent of cystic echinococcosis, possesses a vast number of antigenic peptides that are constantly presented in the host immune system during infection. Here, we sought to provide more information about the cellular/humoral components engaged in the peripheral immune reactions to the fertile-cyst-derived Echinococcus alkaline phosphatase (E.ALP) in human hosts. Lymphoproliferative and cytokine responses after recall of E.ALP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Recent findings have suggested that IL-10 impairs the Th1 protective response and allows the parasites to survive in hydatid patients [ 24 ]. Experimental studies in mice supported the possible local immunosuppression mediated by IL-10 as a possible mechanism that helps the parasites in escaping the host cell-mediated response [ 39 , 40 ]. Our study suggested that higher Th1 and Th17 immune responses were associated with a lower IL-10 mRNA production and miR-374b-5p overexpression, while lower Th1 and Th17 immune responses were associated with a higher IL-10 mRNA production and miR-374b-5p inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have suggested that IL-10 impairs the Th1 protective response and allows the parasites to survive in hydatid patients [ 24 ]. Experimental studies in mice supported the possible local immunosuppression mediated by IL-10 as a possible mechanism that helps the parasites in escaping the host cell-mediated response [ 39 , 40 ]. Our study suggested that higher Th1 and Th17 immune responses were associated with a lower IL-10 mRNA production and miR-374b-5p overexpression, while lower Th1 and Th17 immune responses were associated with a higher IL-10 mRNA production and miR-374b-5p inhibition.…”
Section: Discussionmentioning
confidence: 99%